METODE DZIKIR DALAM PENURUNAN TINGKAT KECEMASAN PADA PASIEN GAGAL GINJAL KRONIK TERHADAP TERAPI HEMODIALISA - Hasanah, Ayu Masrurotul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
One the most common psychological problems found in chronic kidney failure patients urdergoing hemodialisys is anxiety. Anxiety that cannot be overcome can have a negative impact on patient. One of the non-pharmacological techniques to reduce anxiety experienced by patients with chronic kidney failure undergoing hemodialysis is the dhikr method. The research method we use here is a literature review using electronic database through international and national journals such as google scholer, science direct. Pro-quet, jstor with the keyword dhikr method in reducing anxiety levels in patients wiyh chronic kidney failur againts hemodialysis therapi criteria. The inclusion used by the author is to limit the articles or journals published in the last five years starting from 2017to 2021. This literature riview uses 20 articles that meet the criteria. Conclusion regarding the result of the literature review above, one of the methods for reducing anxiety in chronic kidney failure patients undergoing hemodialysis is relaxation techniques such as dhikr.